Malnutrition and oral Health in Elderly: a Narrative Review - Jamas Ari Anggraini; Nuroh Najmi; Anggun Rafisa; Felisa Febriane Balafif; Kartika Indah Sari (Jurnal EduHealth, 2025)
The aging process is generally defined as the accumulation of various changes that occur in cells and tissues as we age. According to the World Health Organization (WHO), an elderly individual is defined as a person who has reached or surpassed 60 years of age. Changes in conditions experienced by the elderly are not only physical changes, but also social and psychological changes. These changes influence each other and interact with other factors, which have an impact on the health conditions of the elderly, including appetite regulation which indirectly also has an impact on nutritional status in elderly. As we already know, nutrition is an important component for the elderly that affects the entire aging process and the general health condition of the elderly, including their oral health. Oral health and nutrition themselves have a multidirectional relationship. This relationship is manifested in the oral cavity, including plaque formation, dental caries, periodontal disease and other oral conditions. It is imperative for clinicians to comprehend the interplay between oral health and nutrition, as this knowledge is crucial for the effective management of elderly patients. This article focuses on the relationship between nutrition an oral health and its impact on older adults.